1996
DOI: 10.1116/1.589151
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of oxide desorption from InSb(001) substrates

Abstract: Thermal desorption of oxide layers from InSb(001) substrates was studied using reflection high energy electron diffraction (RHEED), x-ray photoelectron spectroscopy, Auger electron spectroscopy, and scanning electron spectroscopy. Surfaces of as-loaded substrates prepared using either of two common chemical etchants were composed of oxide layers containing In2O3 and Sb2O5. As the substrate temperature was raised, a multistage desorption process was observed. Most of the Sb2O5 was reduced during the first stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 0 publications
2
26
0
4
Order By: Relevance
“…These binding energies represent the measured energy positions of In and Sb in a stoichiometric InSb material system. The spin-orbit separation and biding energies are in close agreement with those reported by Liu and Santos, 30 who presented detailed XPS, with binding energies, chemical shifts, and Auger spectra obtained from InSb after chemical preparation and during thermal desorption. The composition of the plasma-cleaned InSb (112)B surface was calculated using a standard procedure where a Shirley background subtraction and a five-point smoothing was first applied to the data.…”
Section: He + Plasma Cleaning Of Insb By Icpsupporting
confidence: 88%
See 2 more Smart Citations
“…These binding energies represent the measured energy positions of In and Sb in a stoichiometric InSb material system. The spin-orbit separation and biding energies are in close agreement with those reported by Liu and Santos, 30 who presented detailed XPS, with binding energies, chemical shifts, and Auger spectra obtained from InSb after chemical preparation and during thermal desorption. The composition of the plasma-cleaned InSb (112)B surface was calculated using a standard procedure where a Shirley background subtraction and a five-point smoothing was first applied to the data.…”
Section: He + Plasma Cleaning Of Insb By Icpsupporting
confidence: 88%
“…35 Defects expected from In-Te compound formation are suppressed on the B face 36 without using a Cd overpressure. 35 As such, the observed defects may be attributed to thermal 11,30,37,38 or plasma sputter 37 induced microscopic In islands which may lead to hillock-like growth features. 11 As the relaxed lattice mismatch (Da/a) is small, 0.05%, 36 and a portion is elastically accommodated, 39 low EPD and narrow x-ray diffraction rocking curves are expected.…”
Section: Growth Of Cdte On Insbmentioning
confidence: 90%
See 1 more Smart Citation
“…A detailed series of experiments have been reported using a variety of etches and microscopic analysis of post-etch morphology as well as XPS, RHEED, and AES studies of the surface before, during, and after oxide desorption. (69,70) They found that the etch CP4A (HNO 3 :CH 3 COOH:HF:H 2 O in the ratio 2:1:1:10) produces the flattest surfaces. The surfaces are also protected by a passivating oxide produced by the oxidizing etch.…”
Section: Substrate Preparationmentioning
confidence: 98%
“…[6] It was found that the sulfur treatment of an InSb(100) surface prior to insulator layer deposition results in considerable reduction of the surface charges and improves thermal stability of the performance of metal-insulator-semiconductor devices. [7,8] The surface treatment with an ammonium sulfide solution caused notable photosensitivity enhancement and dark current reduction for InAsSb and InAsPSb photodiodes.…”
Section: Introductionmentioning
confidence: 99%